The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.7759/cureus.48078
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Applications in Spine Surgery

Themistoklis Tragaris,
Ioannis S Benetos,
John Vlamis
et al.

Abstract: This literature review sought to identify and evaluate the current applications of artificial intelligence (AI)/machine learning (ML) in spine surgery that can effectively guide clinical decision-making and surgical planning. By using specific keywords to maximize search sensitivity, a thorough literature research was conducted in several online databases: Scopus, PubMed, and Google Scholar, and the findings were filtered according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…A recent literature review analyzed 46 studies on the applications of AI and ML in spinal surgery [82]. The findings revealed that AI/ML models were accurate, with an average overall value of 74.9%.…”
Section: Surgeriesmentioning
confidence: 99%
“…A recent literature review analyzed 46 studies on the applications of AI and ML in spinal surgery [82]. The findings revealed that AI/ML models were accurate, with an average overall value of 74.9%.…”
Section: Surgeriesmentioning
confidence: 99%